(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study evaluated the effectiveness of a modified Vacuum-Assisted Laser Ablation (VALA) technique in the treatment of large-diameter (18–30 mm) truncal veins. A total of 42 patients were divided into two groups: standard VALA and modified VALA based on a cardiological introducer. During a 180-day follow-up period, the recanalization rate was significantly lower in the modified technique (1.0% vs. 2.5%, p < 0.05). The application of high vacuum pressure ranging from −0.8 to −1.0 bar provided a “dry vein” effect, enhancing the maximal impact of laser energy on the vein wall. The proposed method was found to be effective, safe, and economically justified. Varicose vein disease is one of the most common pathologies of the venous system in the lower extremities, and among modern treatment methods, endovenous laser ablation (EVLA) holds a leading position. However, in large-diameter veins (greater than 18 mm), the risk of recanalization persists even after standard EVLA and conventional VALA procedures. This condition is often explained by incomplete evacuation of blood from the vein lumen and insufficient delivery of laser energy to the vein wall. Although VALA technology partially addresses this issue, technical limitations of existing catheters (narrow aspiration channel, thin port wall, and risk of damage by needle during tumescent anesthesia) restrict its effectiveness. Therefore, studying the efficacy of a high-vacuum modified VALA technique based on a cardiological introducer represents a relevant scientific objective.